Experimental and numerical investigations of cooling drag. (August 2017) - Hobeika, Teddy; Sebben, Simone; Löfdahl, Lennart
As the target figures for CO2 emissions are reduced every year, vehicle manufacturers seek to exploit all possible gains in the different vehicle attributes. Aerodynamic drag is an important factor that affects the vehicle's fuel consumption, and its importance rises with the shift from the New European Driving Cycle to the Worldwide harmonized Light vehicles Test Cycle which has a higher average speed. In order to reduce vehicle drag, car manufacturers employ the use of grill/spoiler shutters which reduces the amount of air going through the vehicle's cooling system, also known as cooling flow, thus reducing both its cooling capability and the resultant cooling drag. This paper investigates the influence of different grill blockages on the cooling flow through the radiator of a Volvo S60. By modifying the engine bay and radiator, load cells are used to measure the force acting on the radiator core while the velocity distribution across the radiator core is measured using pressure probes. These values are analyzed and compared to different vehicle configurations and grill inlet designs. A number of test configurations are reproduced in Computational Fluid Dynamics simulations and compared to the test results. For some grill configurations, the simulations provide a good prediction of mass flow and velocity distribution; however a clear discrepancy is present as the grill blockages increase. On the other hand, the force acting on the radiator core was well predicted for all configurations. This paper discusses the different parameters affecting cooling flow predictions such as wind tunnel blockage and measurement grid discretization by comparing radiator forces and mass flows. In addition, the changes on overall vehicle forces are discussed with the radiator force put in context with cooling drag.